Does the retail hypermarket satisfy customers? market assessment in Malaysia - Chowdhury, Naila Anwar; Haque, A. K. M. Ahasanul; Maulan, Suharni (Research Publishing Academy, 2019)
As competition within the retail industry has intensified, an investigation of the factors that drive customer satisfaction towards hypermarkets has become a burning issue. Customer satisfaction is imperative for attaining organizational sustainability through building long term relationship with customers. Therefore, the current study has been developed to examine the factors that may affect customer satisfaction towards hypermarkets in Malaysia. The study attempts to examine the effects of retailer image, retailer awareness and perceived value on customer satisfaction towards hypermarkets, specifically in the Malaysian setting. In order to obtain these objectives, a conceptual framework has been developed. Data were collected through the distribution of self-structured questionnaires from retail customers located in Klang Valley, Malaysia. Afterwards, data were analysed using SPSS and SEM. The findings unveiled that retailer image, retailer awareness and perceived value have significant effect on customer satisfaction towards hypermarkets. The outcomes of the study will facilitate marketers in devising effective strategies for satisfying customers. From an academic point of view, the study will be a meaningful addition to the literature and aid researchers in undertaking further studies in the future.